Applied artificial higher order neural networks for control and recognition - Zhang, Ming 1949 (Advances in computational intelligence and robotics (ACIR) book series, 2016)
This book explores the ways in which higher order neural networks are being integrated specifically for intelligent technology applications, emphasizing emerging research, practice, and real-world implementation